Antibacterial activity of the non-cytotoxic peptide (p-BthTX-I)2 and its serum degradation product against multidrug-resistant bacteria - Santos-Filho, Norival A. [UNESP] (2017)
Antimicrobial peptides can be used systemically, however, their susceptibility to proteases is a major obstacle in peptide-based therapeutic development. In the present study, the serum stability of p-BthTX-I (KKYRYHLKPFCKK) and (p-BthTX-I)2, a p-BthTX-I disulfide-linked dimer, were analyzed by mass spectrometry and analytical high-performance liquid chromatography (HPLC). Antimicrobial activities were assessed by determining their minimum inhibitory concentrations (MIC) using cation-adjusted Mueller-Hinton broth. Furthermore, biofilm eradication and time-kill kinetics were performed. Our results showed that p-BthTX-I and (p-BthTX-I)2 were completely degraded after 25 min. Mass spectrometry showed that the primary degradation product was a peptide that had lost four lysine residues on its C-terminus region (des-Lys12/Lys13-(p-BthTX-I)2), which was stable after 24 h of incubation. The antibacterial activities of the peptides p-BthTX-I, (p-BthTX-I)2, and des-Lys12/Lys13-(p-BthTX-I)2 were evaluated against a variety of bacteria, including multidrug-resistant strains. Des-Lys12/Lys13-(p-BthTX-I)2 and (p-BthTX-I)2 degraded Staphylococcus epidermidis biofilms. Additionally, both the peptides exhibited bactericidal activities against planktonic S. epidermidis in time-kill assays. The emergence of bacterial resistance to a variety of antibiotics used in clinics is the ultimate challenge for microbial infection control. Therefore, our results demonstrated that both peptides analyzed and the product of proteolysis obtained from (p-BthTX-I)2 are promising prototypes as novel drugs to treat multidrug-resistant bacterial infections.